2013
DOI: 10.1007/978-3-642-44927-7_29
|View full text |Cite
|
Sign up to set email alerts
|

Model and Algorithm for Dynamic Multi-Objective Distributed Optimization

Abstract: Abstract. Many problems in multi-agent systems can be represented as a Distributed Constraint Optimization Problem (DCOP) where the goal is to find the best assignment to variables in order to minimize the cost. More complex problems including several criteria can be represented as a Multi-Objective Distributed Constraint Optimization Problem (MO-DCOP) where the goal is to optimize several criteria at the same time. However, many problems are subject to changes over time and need to be represented as dynamic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“… Other scenarios were Dynamic DCOPs are modelled include collective autonomous vehicles for collision avoidance [ 66 ], human resources reorganisation such as scheduling elective surgery for emergencies in hospitals [ 67 ], distributed controlling of IoT devices and sensors for minimisation of energy consumption in smart homes [ 47 ], and dynamic social simulation through law enforcement problems and market-based mechanisms for dynamic task allocation to agents [ 68 ]. Proposals without scenarios [ 24 , 25 , 39 , 40 , 42 , 43 , 44 , 53 , 54 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ] are the majority of the studies found. These studies refer to possible applications but are merely introductory examples without the context of a specific scenario.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… Other scenarios were Dynamic DCOPs are modelled include collective autonomous vehicles for collision avoidance [ 66 ], human resources reorganisation such as scheduling elective surgery for emergencies in hospitals [ 67 ], distributed controlling of IoT devices and sensors for minimisation of energy consumption in smart homes [ 47 ], and dynamic social simulation through law enforcement problems and market-based mechanisms for dynamic task allocation to agents [ 68 ]. Proposals without scenarios [ 24 , 25 , 39 , 40 , 42 , 43 , 44 , 53 , 54 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ] are the majority of the studies found. These studies refer to possible applications but are merely introductory examples without the context of a specific scenario.…”
Section: Resultsmentioning
confidence: 99%
“…Proposals without scenarios [ 24 , 25 , 39 , 40 , 42 , 43 , 44 , 53 , 54 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ] are the majority of the studies found. These studies refer to possible applications but are merely introductory examples without the context of a specific scenario.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations